Fabrication and Characterization of C60-Based Organic Schottky Diodes - 程晓曼 胡子阳 吴仁磊 王忠强 印寿根 (Chinese physics letters, 2010)
We have fabricated organic Schottky barrier diodes with Cu/LiF/C60/Al andwiched construction. Cu and Al are selected as the cathode and the anode, respectively. C60 is used as the organic layer and LiF as the buffer layer inserted between the cathode and C60. After the annealing process, Schottky contact is well formed at the Al/C60 interface and Ohmic contact is formed at the （Cu/LiF）/C60 interface. The current density-voltage （J-V） measurements of the diodes present nonlinear behavior. As a result, the rectification ratio reaches 1×03. The characteristics of the diodes have been analyzed using the energy band diagram. The values of Schottky barrier height ΦB, ideality factor n and reverse saturation current density Js are extracted according to the standard thermionic emission model.